Tinjauan Yuridis Terhadap Penanggulangan Tindak Pidana Perdagangan Manusia Di Indonesia Dan Filipina - Rina Shahriyani Shahrullah; Dedy Febriyanto Tjhang (Journal of Judicial Review, 2014)
Along with urbanization and globalization are growing and developing so rapidly, in addition to a positive impact, but also bring negative influence including Trafficking in persons, or human trafficking. Trafficking itself is a cruel crime that violates human dignity and a violation of human rights of the most concrete and often prey on those who are weak economically, socially, politically, culturally and biologically. Trafficking is not only happening in Indonesia alone but also in the Philippines and just like Indonesia is source country, so that this crime be a global problem.A convention has been created and produced the Palermo Protocol to combat Trafficking which has been ratified by both countries. This study describes clearly and carefully about combat trafficking system (Prosecution, Protection, and Prevention) against human trafficking both countries with their salty legal provisions.This research is a normative juridical law by using the method of comparative law. Data used in the form of secondary data. Data mining is done with literature (library research). After all the data is collected, the data is then processed and analyzed, then used the qualitative analysis point by grouping the data aspects studied. Furthermore, the conclusions drawn related to this research, then described descriptively.Based on this study showed that in terms of countermeasures against crimes recorded although there are more crimes in the Philippines than in Indonesia but the government of the Philippines showed a significant increase in combating human trafficking crimes compared with Indonesia.